Comparison of efficacy of intra-articular morphine and steroid in patients with knee osteoarthritis - Beyaz, Serbülent Gökhan (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: Primary therapeutic aim in treatment of osteoarthritis of the knee is to relieve the pain of osteoarthritis. The aim of this study was to compare the efficacy of intra-articular triamcinolone with intra-articular morphine in pain relief due to osteoarthritis of the knee in the elderly population. MATERIALS AND METHODS: Patients between 50 and 80 years of age were randomized into three groups. Group M received morphine plus bupivacaine intra-articularly, Group T received triamcinolone plus bupivacaine intra-articularly, and Group C received saline plus bupivacaine intra-articularly. Patients were evaluated before injection and in 2nd, 4th, 6th, and 12th weeks after injection. First-line supplementary analgesic was oral paracetamol 1500 mg/day. If analgesia was insufficient with paracetamol, oral dexketoprofen trometamol 50 mg/day was recommended to patients. RESULTS: After the intra-articular injection, there was statistically significant decrease in visual analog scale (VAS) scores in Groups M and T, when compared to Group C. The decrease of VAS scores seen at the first 2 weeks continued steadily up to the end of 12th week. There was a significant decrease in Groups M and T in the WOMAC scores, when compared to Group C. There was no significant difference in the WOMAC scores between morphine and steroid groups. Significantly less supplementary analgesics was used in the morphine and steroid groups. CONCLUSION: Intra-articular morphine was as effective as intra-articular triamcinolone for analgesia in patients with osteoarthritis knee. Intra-articular morphine is possibly a better option than intra-articular steroid as it has lesser side effects.